The Effects of Aromatherapy on Anxiety and Depression in People With Cancer: A Systematic Review and Meta-Analysis - Li, Dan; Li, Yuxin; Bai, Xue; Wang, Meijuan; Yan, Jingzheng; Cao, Yingjuan (Frontiers in Public Health, 2022)
Background Anxiety and depression are highly prevalent in people with cancer. Medical therapies are usually prescribed to alleviate anxiety and depression, but they are associated with a variety of adverse effects. Recently, aromatherapy showed potential as a complementary medicine to improve psychological health and wellbeing. However, its effectiveness on relieving anxiety and depression has not been established. Objective This study explored the beneficial effects of aromatherapy on psychological symptoms such as anxiety and depression in people with cancer. Methods We searched international databases including PubMed, Web of Science, Cochrane Library, Embase, Medline, Ebscohost, ProQuest and Scopus from inception to 31 May 2021. The risk of bias was assessed using the Cochrane Collaboration's tool for assessing risk of bias. The systematic review and meta-analysis were performed according to the PRISMA guidelines. Quantitative analysis was performed on the studies that met our inclusion criteria, and Meta-analysis was performed on the studies with available data by RevMan software. Results The quality of the literatures were assessed carefully by two researchers, a total of 17 studies were included in the systematic review and 10 articles were conducted in meta-analysis. The aromatherapy was effective in relieving anxiety (SMD = −0.49, p < 0.05) in people with cancer. Subgroup analysis suggested that most effective methods were aromatic massage (SMD = −0.70, p < 0.005), aromatherapy with lavender essential oils (SMD = −1.12, p < 0.01), short-time interventions (duration < 4weeks) (SMD = −0.87, p < 0.05) and studies in Asia (SMD = −0.83, p < 0.05). Regarding depression and psychological wellbeing, there were no difference between aromatherapy and control groups. Conclusion In cancer patients, the aromatherapy was effective for relieving anxiety. However, there was no beneficial effect on depression and psychological wellbeing. Systematic Review Registration PROSPERO, identifier: CRD42021272465.